Le e-commerce, facteur d’atténuation des iniquités territoriales en termes d’offre commerciale ? - Lucie Sieys; Marie Huyghe; Hervé Baptiste (Netcom)
E-commerce is a recent tool which offers everyone the possibility to buy and sell all sorts of goods and services on a virtual platform. In theory, therefore, it has the potential to palliate spatial disparities of accessibility to commerce that can be observed between urban, peri-urban and rural communities. Our article aims to analyse the way in which e-commerce is used in different types of territory: we shall highlight a similarity in the practices of households, whatever their territory of residence may be. We shall interpret these similarities by means of practices of ease of mobility (fast and inexpensive) which today enable the majority of households to have access to traditional businesses.